Behavioral and Psychosocial Characteristics Among Head Start Childcare Providers. (December 2018) - Ling, Jiying
The aim of the study was twofold: (a) describe behavioral and psychosocial characteristics of Head Start childcare providers including technology use, physical activity, nutrition, depression, and quality of life and (b) examine associations among these characteristics. Using a cross-sectional design, a nonrandom sample of 80 Head Start childcare providers completed an online survey via SurveyMonkey. About 80.1% were overweight or obese. Nearly all had a computer or smartphone. About 55% met the national physical activity recommendation of 150 min/week. Approximately 56.2% did not know the recommended daily servings of fruits and vegetables, and 26.3% had ≥3 servings of vegetables per day. About 38.8% had major depression or dysthymia, and 31.3% had depressive symptoms. The top two perceived health needs were weight loss and stress management. Providing a health promotion and stress management program to childcare providers may benefit both providers and children, considering the strong influence of teachers on children.